(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
Drawing loosely on Richard Dyer’s approach to the study of film stardom, this article aims to reconstruct the complex discursive articulation that characterizes the star image of Adriano Celentano between 1962 and 1965. During this period, the Milanese singer shifts definitively from the model of the “urlatore” to the new and more layered image of the good, hard- working and successful young man. Specific focus is dedicated to the relationship between this new image of Celentano and the processes of “reformation” of traditional masculinity that mark the Italian society of the Sixties.